Awareness of Basic Life Support among Speech and Hearing Professionals - Suman, Ankita; Neupane, Anuj Kumar; Chowdhury, Arpita Singha (Journal of Health and Allied Sciences NU, 2023)
Introduction One of the most important aspects of happiness is one's health. Increased industrialization in developing nations has contributed to a change in disease patterns away from infectious illness as the major cause of morbidity and mortality toward chronic diseases such as heart disease and trauma. Most emergency circumstances need immediate medical attention before a person is taken to the hospital; therefore, public awareness and training programs can aid in providing efficient basic life support care and services. Only a few works of literature on basic life support and prehospital emergency care in an Indian context are available and are usually studied among school teachers. However, no comparable research including allied health experts such as speech and hearing professionals has yet been published in the literature.Aim The present study aimed at exploring the awareness of speech and hearing professionals regarding basic life support in an Indian context.Methods The questionnaire consisted of two sections where section A comprised 6 questions related to demographic details and participant's experience, and section B composed of 17 questions related to knowledge of normal bodily physiology, medical emergencies, and first aid and related aspects. A cross-sectional exploratory study design was conducted on 250 participants. Out of 250 responses, 42 of them were incomplete and so were removed from the study. Therefore, a total of 208 complete responses received from the participants in the age range of 22 to 60 years from across 23 states and 1 union territory of India were included in the study.Results The result revealed a low percentage of speech and hearing professionals with an adequate understanding of basic life support. The majority of them were found to have insufficient knowledge of normal bodily physiology, medical emergencies, and first aid and related aspects.Discussion Being the first of its kind, the present study revealed limited awareness about basic life support among professionals, and therefore, the need to improvise the knowledge of basic life support and prehospital emergency care. This may be achieved by introducing training programs of various natures and dimensions to speech and hearing professionals.
Keywords: basic life support; emergency care; first aid; medical emergencies; bodily physiology; speech and hearing